Analisis dan Perbaikan Sistem Pencahayaan Buatan pada Rumah Sakit Tipe C di Kota Semarang dengan Menggunakan Simulasi Software Dialux Evo 11.1 - Rachmawan, Rizky Firdaus; Kanata, Sabhan; Sumarno, Radiktyo Nindyo (Universitas Al Azhar Indonesia, 2024)
The need for electrical energy is increasing due to population growth and the use of electrical equipment, including lighting systems or lamps. Lighting systems or lamps are important factors in creating a comfortable, safe and efficient atmosphere in the work environment, especially hospitals. Various methods have been used so that the lighting system or lamps can be optimized, for example by analyzing through Dialux Evo simulation. This study analyzes and improves the lighting system in a Type C hospital in Semarang using the Dialux Evo 11.1 simulation. The focus is on the nutrition or surgical polyclinic room and the operating room. The research method involves a comparison between the results of lighting strength measurements and simulations with the SNI 6197: 2011 standard. The measurement results show that the polyclinic room has an average lighting of 91.61 lux, while the simulation reaches 127 lux. For the operating room, the measurement produces 81.52 lux and the simulation 274 lux. Both of these rooms do not meet the minimum standards: 250 lux for the polyclinic room and 300 lux for the operating room. For the recommended improvements in the polyclinic room is the addition of 4 Philips LED-Tube 765 T8 AP C G light points or 5 Philips Downlight DN020B G3 D150 light points. While for the operating room, it is recommended to replace 14 points with Philips LED-Tube UO 16W865 T8 lights.Keywords - Lighting System, Strong Lighting, Dialux Evo 11.1, SNI 6197:2011